Small Perturbations of an Indefinite Elliptic Equation - Ramos-Quoirin, H (Wiley-VCH Verlag, 2015)
We investigate a perturbed semilinear indefinite elliptic equation and show that the results known for the unperturbed equation still hold if the perturbation is sufficiently small. To this end, we use a continuity argument that allows us to establish the existence of two positive solutions even in the case where the strong maximum principle does not apply. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.